Bibliometric Analysis and Systematic Literature Review: Effective Decision Making with the Help of Accounting Information - Purwianti, Ari; Cholifah, Emilia Nur; Handayati, Puji; Restuningdiah, Nurika (Journal of Applied Business, Taxation and Economics Research, 2025)
In an increasingly complex and competitive digital era, effective decision-making is a key challenge for organizations and companies. Accounting information, as a source of financial and non-financial data, is considered crucial to support the process. However, constraints in data access, integration, and utilization often hinder informed and rapid decision-making. To understand the trends and contributions of research in this field, this article uses bibliometric analysis and systematic literature review methods. Data were obtained through searching for articles related to accounting information systems and decision-making from the Web of Science database, with a time limit of 2019-2025 and certain relevance criteria. The results of the analysis show that related publications are increasing rapidly, with the main focus on the role of accounting information systems in improving management effectiveness and strategic decision making. Other findings show that the use of Big Data and digital technology in accounting information systems can improve data quality, minimize risks, and increase organizational transparency and accountability. Thus, the utilization of appropriate and integrated accounting information systems is essential to support more.